Development of placement test instruments for assessing BIPA reading ability - Izdiharti Husniyah; Didin Widyartono (Jurnal Bahasa Indonesia bagi Penutur Asing, 2022)
The development of a valid and reliable placement test instrument is very much needed in line with the increasing interest in BIPA (Indonesian for Speakers of Other Languages). This research aims to produce a placement test instrument for BIPA students' reading skills. This study uses the Research and Development (R&D) method with a 3D model (define, design, and develop). The products produced are test instruments, competence indicators, scoring, and placement guides. The test instrument consists of three packages of questions, and each package consists of 30 multiple-choice questions. The development of test questions is based on competency standards in the book "Sahabatku Indonesia untuk Umum" by PPSDK 2019. Product validation was carried out by two experts (assessment and BIPA), while the trial was conducted on ten BIPA students. The results of the validation and testing showed that the test was able to place students according to their reading ability level